New perspectives on H.R. Haggard: from South Africa to the Imperial Dream - Patricia CROUAN-VÉRON (E-REA)
H. R. Haggard dedicated Nada the Lily (1892), the first romance of his Zulu trilogy1 to Theophilus Shepstone. He considered Shepstone as his mentor, having met him in South Africa at the age of nineteen while he was working with Sir Henry Bulwer-Lytton as an aide-de-camp. With them and accompanied by Mazooku and other local people they travelled through Natal crossing wonderful landscapes but experiencing very harsh conditions. As Haggard declared “It [was] no place for Cook’s tourist!” (Haggard Diary 209). Haggard’s first stay in Natal lasted seven years and this experience played a determining role in Haggard’s life and in his writing of imperial romances. Studying Haggard’s fiction from the South African angle leads us to question his vision of imperialism. To what extent did his personal experience of South Africa model his vision of the Empire and how did he come to write imperial romances? How did he reconcile the apparent contradiction of being a “man of action” and a “man of letters”? Why is the land issue so determining in this vision? These are some questions we will try to answer to show that Haggard’s complexity is part of his modernity and is also probably the key to his legacy.